2015
DOI: 10.1161/circimaging.115.003020
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Pathophysiology and Prognosis

Abstract: of the LA in AF, CT and CMR imaging also provide volumetric measures. Notably, CT and CMR consistently yield higher LA volume compared with 2D echocardiography, and a goldstandard modality has not been established. 28 The same holds true for comparisons of 3D echocardiography and CMR. 29(Circ Cardiovasc Imaging. 2015;8:e003020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 112 publications
(103 reference statements)
2
11
0
Order By: Relevance
“…9,10 Chronic RA pressure overload and stretching, along with chronic hypoxia, may alter the atrial substrate by promoting fibrosis and local tissue heterogeneities, which in turn predispose to a risk for AF. 19 This is consistent with emerging data demonstrating a key role of atrial fibrosis in the pathogenesis of AF as documented by delayed enhancement on MRI. 20,21 Figure 2 with those from 16 age-matched controls without PH undergoing EPS for supraventricular tachycardia.…”
Section: Pathophysiology Of Atrial Arrhythmias In the Setting Of Elevsupporting
confidence: 90%
“…9,10 Chronic RA pressure overload and stretching, along with chronic hypoxia, may alter the atrial substrate by promoting fibrosis and local tissue heterogeneities, which in turn predispose to a risk for AF. 19 This is consistent with emerging data demonstrating a key role of atrial fibrosis in the pathogenesis of AF as documented by delayed enhancement on MRI. 20,21 Figure 2 with those from 16 age-matched controls without PH undergoing EPS for supraventricular tachycardia.…”
Section: Pathophysiology Of Atrial Arrhythmias In the Setting Of Elevsupporting
confidence: 90%
“…[15][16][17][18] Studies in nononcology patients have further shown that echocardiographic measures of left atrial (LA) dysfunction (eg, low LA ejection fraction [EF] and abnormal reservoir strain) may provide incremental value in determining future AF risk. 19,20 There is a paucity of information on the incidence and risk factors of de novo AF in HCT patients, especially in those undergoing allogeneic HCT, and there have been no studies to examine the association between pre-HCT echocardiographic parameters and future AF risk. In these patients, it is especially important to understand outcomes following the onset of AF, given the increasing indications for HCT and greater numbers of older (.…”
Section: Introductionmentioning
confidence: 99%
“…During AF, the ineffective contraction of the left atrium promotes vascular stasis, which, along with the pro coagulating state, produces an increase in the formation of thrombi at the level of the left atrial appendix, a remnant of sac-shaped embryonic development that would contribute to the cardiovascular risk of AF (36,37). Other prothrombotic abnormalities in patients with AF include alterations in the D-dimer, platelet factor-4, thrombin-antithrombin complexes, and plasminogen activator inhibitor (PAI-1).…”
Section: Atrial Fibrillation and Cardiovascular Riskmentioning
confidence: 99%